Persistent glucose production during glucose infusion in the neonate. - Cowett, R M (1983)
In adults, glucose infusion results in a decreased glucose production rate (GPR) as a mechanism for maintaining euglycemia. To document the development of glucose homeostasis, we derived the GPR in 23 preterm appropriate for gestational age infants, 14 term appropriate for gestational age infants, and in 6 adults. After a 3-h fast, the average plasma glucose and insulin concentration was measured and the GPR was derived. During glucose infusion (5.6 +/- 0.3 mg X kg-1 min-1), compared with saline controls, the preterms had a rise in plasma glucose and plasma insulin, and the GPR was 1.4 mg X kg-1 min-1 (range, 0-4.4) vs. 3.0 mg X kg-1 min-1 (range, 1.8-4.1) (saline controls). In the term infants, only the plasma insulin concentration was elevated when the glucose infused (5.7 +/- 0.3 mg X kg-1 min-1) infants were compared with the saline controls and GPR was 0.4 X kg-1 min-1 (range, 0-2.6) vs. 3.4 mg X kg-1 min-1 (range, 2.8-5.7) (saline controls). In comparison to saline infused adults, glucose infusion (3.2 +/- 0.1 mg X kg-1 min-1) resulted in a significant rise in plasma glucose and in plasma insulin; and the GPR was reduced to 0.1 mg X kg-1 min-1 (range, 0-0.3) from 2.0 mg X kg-1 min-1 (range, 1.5-2.4). 5 of 13 preterms and 2 of 7 term infants had persistent GPR during glucose infusion; in contrast, the GPR in all adults was unmeasurable. There was no correlation between the plasma glucose concentration and the GPR in the newborn or in the adult. Both newborns and adults did have a correlation between plasma insulin concentration and the GPR; however, there was considerable variability in the neonate. We conclude that there are significant developmental differences in neonatal glucose homeostasis and that insulin is important in neonatal hormonal control of glucose production.